Thermal and Optical Analysis of Glazing Systems Manufactured in Cyprus - Kalogirou, Soteris A.; Florides, Georgios A. (My University, 2005)
For the accurate determination of the building thermal load, it is very important to be able to determine the characteristics of fenestration products correctly. These are usually determined from handbooks without considering the size of the glass and the characteristics of the frame. In the present paper a survey of the available products, manufactured in Cyprus, is presented from which 14 typical glazing systems are obtained (7 windows and 7 doors). These glazing systems are analyzed with Therm v.5.2 and Window v.5.2 software and the thermal and optical characteristics are presented. Both programs are considered very accurate in performing this type of estimations. Thus with the present methodology, a more accurate estimation of the glazing coefficients is obtained. The results indicate that the new values calculated are 3-39% higher than the handbook values depending on the size of the glass. Also investigated are the effects of window size and use of wooden frames on the U-value.
Keywords: Thermal analysis; Optical analysis; Glazing systems